UDP-glucose: β-(1-3)-glucan (paramylon) synthase from Euglena gracilis - Van der Merwe, Laurianne (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Plant Biotechnology))--University of Stellenbosch, 2007.